Macrophage metabolism in nonalcoholic fatty liver disease - Zhang, Wenhui; Lang, Ren (Frontiers in Immunology, 2023)
Nonalcoholic fatty liver disease (NAFLD) and its inflammatory and often progressive subtype nonalcoholic steatohepatitis (NASH), have emerged as significant contributors to hepatic morbidity worldwide. The pathophysiology of NAFLD/NASH is multifaceted, variable, and remains incompletely understood. The pivotal role of liver-resident and recruited macrophages in the pathogenesis of NAFLD and NASH is widely acknowledged as a crucial factor in innate immunity. The remarkable plasticity of macrophages enables them to assume diverse activation and polarization states, dictated by their immunometabolism microenvironment and functional requirements. Recent studies in the field of immunometabolism have elucidated that alterations in the metabolic profile of macrophages can profoundly influence their activation state and functionality, thereby influencing various pathological processes. This review primarily focuses on elucidating the polarization and activation states of macrophages, highlighting the correlation between their metabolic characteristics and the transition from pro-inflammatory to anti-inflammatory phenotypes. Additionally, we explore the potential of targeting macrophage metabolism as a promising therapeutic approach for the management of NAFLD/NASH.